2022
DOI: 10.3390/bios12020115
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanowires Length and Numbers Dependence on Sensitivity of the Field-Effect Transistor Sensor for Hepatitis B Virus Surface Antigen Detection

Abstract: Silicon nanowire field effect transistor (NWFET) sensors have been demonstrated to have high sensitivity, are label free, and offer specific detection. This study explored the effect of nanowire dimensions on sensors’ sensitivity. We used sidewall spacer etching to fabricate polycrystalline silicon NWFET sensors. This method does not require expensive nanoscale exposure systems and reduces fabrication costs. We designed transistor sensors with nanowires of various lengths and numbers. Hepatitis B surface antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…1f). 29 The greatest advantage of this technique is its selfalignment ability. With well-controlled etching parameters, this enabled the production of nanowires less than 100 nm in diameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1f). 29 The greatest advantage of this technique is its selfalignment ability. With well-controlled etching parameters, this enabled the production of nanowires less than 100 nm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…That is, they can be mass-produced to reduce costs and miniaturized to fabricate portable multifunctional biosensors. 29 In this study, a polycrystalline silicon (poly-Si) NWFET biosensor was developed for SARS-CoV-2 detection. As opposed to monocrystalline silicon nanowire, in which expensive silicon-oninsulator chips must be used, ordinary silicon chips can be used as the substrate in poly-Si nanowire devices, greatly reducing manufacturing costs.…”
mentioning
confidence: 99%
“…Furthermore, the chemical functionalization techniques of the pSiNWFET surface were performed for the immobilization of the relevant antibodies for sensing the HBV-related biomarkers such as HBsAg and HBx proteins. These semiconductor biosensors can detect the HBsAg and HBx proteins at the femto-molar level providing an opportunity to evaluate and understand hepatitis infection [40,57] Uhme et al [58] demonstrated that the ultrasensitive electrical detection of the HA1 domain of hemagglutinin (HA), a representative viral surface protein of the influenza virus, using the top-down complementary metal oxide semiconductor (CMOS) processed silicon nanowire (SiNW) field-effect transistor (FET) configuration. Femtomolar concentrations of HA1 can be detected (ΔV T = 63 mV/dec, ΔV T = 112 mV at 1 fM HA1) by virtue of the stable and efficient cytidine-5′-monophospho-N-acetylneuraminic acid(CMP-NANA) probe and intermediate glutaraldehyde(GA) linker, and the high surfaceto-volume ratio of the SiNWs [58] Wu et al used sidewall spacer to fabricate polycrystalline silicon NWFET sensors.…”
Section: Advance In Silicon Nanowire-based Biosensorsmentioning
confidence: 99%
“…To further advance the detection properties of SiNW biosensors, the effects of various critical components on the sensitivity (including the NW structure, , functionalization method, electrolyte ion concentration, , and analyte delivery system) have been investigated by numerous theoretical and experimental studies. The SiNW surface functionalization and biorecognition elements are crucial for the sensitivity and selectivity progress.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that device sensitivity increases with decreasing number of NWs, narrower NW diameters, and lower NW doping densities. Wu 21 analyzed the NW length and number dependence on the sensitivity of the SiNW biosensor and found that sensitivity can be increased by using few SiNWs in biosensors. Owing to these reports, the dependence of NW width, length, number, and doping density on sensitivity has been revealed and investigated.…”
Section: Introductionmentioning
confidence: 99%